Catalyst free removal of trithiocarbonate RAFT CTAs from poly(vinylpyridine)s using tris(trimethylsilyl)silane and light. Issue 37 (15th September 2020) - Fultz, Brandon A.; Beery, Drake; Coia, Brianna M.; Hanson, Kenneth; Kennemur, Justin G.
Abstract : Trithiocarbonate end groups on various polymers, including polyvinylpyridines, are reduced rapily and quantitatively using only tris(trimethylsilyl)silane and light. Abstract : Tris(trimethylsilyl)silane (TTMSS) is introduced as a non-toxic and kinetically superior hydrogen source for the photo-driven reduction of trithiocarbonates from poly(methyl methacrylate), polystyrene, and poly(vinyl pyridine)s (PVP)s created through RAFT polymerization. No other reagents were necessary and quantitative reduction is achieved under UV- and blue-light irradiation. PVP reduction and sequestering of chain combination events is investigated for the first time.